2022
DOI: 10.3389/fendo.2022.1053103
|View full text |Cite
|
Sign up to set email alerts
|

Cocultivation of Chinese prescription and intestine microbiota: SJZD alleviated the major symptoms of IBS-D subjects by tuning neurotransmitter metabolism

Abstract: ObjectiveDiarrhea-predominant irritable bowel syndrome (IBS-D) is a recurrent and common disease featuring dysbiotic intestinal microbiota, with limited treatments. Si-Jun-Zi Decoction (SJZD), a classic Chinese prescription, has been extensively used for IBS-D. This work aimed to explore the ex vivo interactions of SJZD and IBS-D’s intestinal microbiota.MethodsFive samples of intestinal microbiota collected from IBS-D volunteers and five age-matched healthy controls were recruited from the Affiliated Hospital,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Another study reported that the abundance of Streptococcus in the mucosa-associated microbiota is relatively high in Japanese patients with IBS-C [45]. Later, Xia et al [46] suggested a synergistic pattern of neurotransmitter metabolism between Streptococcus and Shigella, a member of the family Enterobacteriaceae, in patients with IBS-D. An exploration of gutMGene [47] showed that members of this taxon are negatively correlated with the expression of several chemokine genes, some of which have reported antimicrobial properties, a phenomenon that may also partly explain differences in Streptococcus abundance. Streptococcus deserves attention in IBS and perhaps other digestive ailments.…”
Section: Discussionmentioning
confidence: 96%
“…Another study reported that the abundance of Streptococcus in the mucosa-associated microbiota is relatively high in Japanese patients with IBS-C [45]. Later, Xia et al [46] suggested a synergistic pattern of neurotransmitter metabolism between Streptococcus and Shigella, a member of the family Enterobacteriaceae, in patients with IBS-D. An exploration of gutMGene [47] showed that members of this taxon are negatively correlated with the expression of several chemokine genes, some of which have reported antimicrobial properties, a phenomenon that may also partly explain differences in Streptococcus abundance. Streptococcus deserves attention in IBS and perhaps other digestive ailments.…”
Section: Discussionmentioning
confidence: 96%